Pengaruh Kelincahan, Keseimbangan, dan Kecepatan Reaksi Terhadap Kemampuan Dribble Bola - Pratama, Bayu Ardi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this research is to know, are there any influence from agility, balance, andspeed reaction to dribble skill in football game of klub Poerce FC Pemalang in 2014/2015.This research is non experimental, which method is survey test and its design is one shotmodel. In this research, the variable is free variable which contains agility, balance, and speedreaction, whereas (variabel terikat) is dribble skill. Population of the research is all player ofKlub Poerce FC Pemalang. Because the number of population is small, so the taking of thesample use total sampling technique, which take all population of klub Poerce FC Pemalangplayer, the total of players are 20 as research sample. Accumulation of research data use testand measuring. Can be conclude that there is an influence between agility, balance, and speedreaction to dribble skill.